The migration ecology of birds - Newton, Ian, 1940- (ScienceDirect, 2008)
This book presents an up-to-date, detailed and thorough review of the most fascinating ecological findings of bird migration. It deals with all aspects of this absorbing subject, including the problems of navigation and vagrancy, the timing and physiological control of migration, the factors that limit their populations, and more. Author, Ian Newton, reveals the extraordinary adaptability of birds to the variable and changing conditions across the globe, including current climate change. This adventurous book places emphasis on ecological aspects, which have received only scant attention in previous publications. Overall, the book provides the most thorough and in-depth appraisal of current information available, with abundant tables, maps and diagrams, and many new insights. Written in a clear and readable style, this book appeals not only to migration researchers in the field and Ornithologists, but to anyone with an interest in this fascinating subject. * Hot ecological aspects include: various types of bird movements, including dispersal and nomadism, and how they relate to food supplies and other external conditions * Contains numerous tables, maps and diagrams, a glossary, and a bibliography of more than 2,700 references * Written by an active researcher with a distinguished career in avian ecology, including migration research.